A systematic review on fatigue analysis in triceps brachii using surface electromyography. (February 2018) - Hussain, Jawad; Sundaraj, Kenneth; Low, Yin Fen; Kiang, Lam Chee; Sundaraj, Sebastian; Ali, Md. Asraf
Abstract: Objective: The objective of this research was to summarize and analyse the research findings regarding analysis of fatigue in the human triceps brachii (TB) muscle through surface electromyography (sEMG) observations. Methods: We systematically searched through five major online scientific databases namely the PubMed, Science Direct, Wiley Online, Springer Link and SCOPUS databases, for articles written in the English language from the year 2001 to March 2017. We specifically searched for the words/phrases "surface electromyography" OR "sEMG" AND "muscle fatigue" AND "triceps" in the title, abstract and keywords to narrow our search and identified 291 articles, of which, 52 were found potentially the most relevant. Results: Of 52 considered articles, 11 analysed fatigue in sports, 11 investigated rehabilitation, 15 considered exercises or trainings, 5 used TB as a co-activator or antagonist, and 5 contemplated elbow extension movements. In addition, 4 of the articles investigated both elbow flexors and extensors and 1 studied training effects in rehabilitation. Conclusion: Although, many studies in this particular field have considered the TB, further investigations are required to explain some specific facts about fatigue in the TB. The compensation strategy that muscles use to overcome fatigue, the stabilization, overcoming of errors during fatigue along with effect of mental load on brachii muscles and the effect of sports drinks and other eatables on fatigue are a few potential zones that require further in-depth research. This study will guide and direct new researchers to areas that remain hidden.